“Exposing force”: the COVID-19 pandemic and women's sport in Ireland during 2020–2021 - Crosson, Seán; Ní Chumhaill, Maedhbh (Frontiers in Sports and Active Living, 2023)
Introduction An analysis of how the pandemic served to highlight neglected weaknesses and inequalities with regard to the structures and supports available to facilitate women's sport in Ireland. Methods A survey conducted in the summer of 2021 with 194 female athletes across the island of Ireland. These athletes were engaged with the sports of camogie, Ladies Gaelic football, hockey, and rugby, and each responded to a 28-question survey. Results Our findings indicate that the experiences of female athletes during the COVID-19 pandemic raise serious questions regarding equality in sport across gender lines. Concerns expressed by the surveyed athletes, especially in relation to access to facilities, inadequate sponsorship, and funding reveal salient aspects of the experiences of Irish female athletes during the pandemic, and its role as an “exposing force” of inequalities within Irish sport. Conclusion The COVID-19 pandemic in Ireland has been a challenging and revealing period with regard to sport in Ireland, acting as an “exposing force” of the existing inequitable structures for both the support and coverage of women's sport. Such challenging periods can also offer opportunities to learn, progress and improve and already in the past year there is evidence of positive developments for women's sport in Ireland, developments that we contend were expedited due to the impact of the COVID-19 pandemic in Ireland.